From Innovation to Pricing: Examining the Mediating Role of Product Quality in SME Coffee Shops - Reno Catelya Dira Oktavia; Amrullah Amrullah; Oktovianus Oktovianus; Adam Rachmatullah; Hanafi Hamzah (Jurnal Penelitian Pariwisata, 2026)
In recent years, small and medium-sized coffee shops have faced intense competition, requiring innovative strategies to enhance product quality and pricing decisions. This study examines the effect of product innovation on price, with product quality as a mediating variable, in SME coffee shops in Jakarta, Indonesia. The purpose of this study is to clarify how innovation translates into price through improvements in product quality, providing both theoretical and practical insights for competitive market management. A quantitative approach was employed, using a survey of 500 coffee shop consumers, which was analysed using Structural Equation Modelling (SEM) with SmartPLS 4. The results indicate that product innovation significantly improves product quality, enhancing menu variety, taste consistency, and overall customer experience. Product innovation also has a significant direct effect on price, while product quality positively influences price. Mediation analysis shows that product quality does not mediate the relationship between product innovation and price. These findings suggest that product innovation primarily drives differentiation and perceived value, but its impact on price through product quality is not significant. The study contributes to marketing and innovation literature by clarifying the relationships linking product innovation, product quality, and price. Practically, SME coffee shop managers are encouraged to integrate product innovation with quality management to strengthen competitive positioning and set prices effectively. Keywords: product innovation; product quality; price; SME coffee shops